2020
DOI: 10.3389/fonc.2019.01548
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Level CT Radiomics Features Preoperatively Predict Lymph Node Metastasis in Esophageal Cancer: A Multicentre Retrospective Study

Abstract: Background: Lymph node (LN) metastasis is the most important prognostic factor in esophageal squamous cell carcinoma (ESCC). Traditional clinical factor and existing methods based on CT images are insufficiently effective in diagnosing LN metastasis. A more efficient method to predict LN status based on CT image is needed. Methods: In this multicenter retrospective study, 411 patients with pathologically confirmed ESCC were registered from two hospitals. Quantitative image features including handcrafted-, comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 42 publications
0
37
0
Order By: Relevance
“…Similarly, some studies have suggested that PKM2 can be used as a prognostic marker for pancreatic ductal cell carcinoma (PDCA), breast cancer, hepatocellular carcinoma (HCC), and gallbladder carcinoma [23][24][25]. In addition, lymph node metastasis is the most important prognostic factor in ESCC [26], accurate nodal staging is crucial for ESCC [27]. Our study showed that PKM2 over-expression promoted lymph node metastasis of ESCC, suggesting that PKM2 may be a molecular target for lymph node metastasis of ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, some studies have suggested that PKM2 can be used as a prognostic marker for pancreatic ductal cell carcinoma (PDCA), breast cancer, hepatocellular carcinoma (HCC), and gallbladder carcinoma [23][24][25]. In addition, lymph node metastasis is the most important prognostic factor in ESCC [26], accurate nodal staging is crucial for ESCC [27]. Our study showed that PKM2 over-expression promoted lymph node metastasis of ESCC, suggesting that PKM2 may be a molecular target for lymph node metastasis of ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…The major advantage of deep learning-based feature extraction is that no specific domain knowledge is required for feature engineering, and the representative and high-level features can be learned in a completely automatic manner. Recent works [ 88 , 89 ] have shown that the automatically learned deep features of neural networks can outperform the hand-crafted ones in some applications. One key challenge of applying deep networks in clinical decision making is that deep networks are black box models with multilayer nonlinear operations, thus the reasoning behind the results from deep networks are very difficult to interpret clinically.…”
Section: Machine Learning and Radiomics Workflow For Oncology Imagingmentioning
confidence: 99%
“…There were four studies [ 88 , 118 , 119 , 120 ] focusing on the lymph node metastasis status of EC, with three studies using CT and one study using MRI. Shen et al [ 120 ] built a nomogram incorporating radiomics features, CT-reported suspicious lymph node number and tumor location, which showed good discrimination of lymph node status with a C-index of 0.75 in the validation set.…”
Section: A Review Of Literature Using Machine Learning and Radiomics mentioning
confidence: 99%
“…15,[17][18][19][20][21] However, hand-crafted features are low-order and susceptible to noise, and may not be adequate for unveiling the characteristics of tumors. 22 Currently, deep learning based on a neural network structure has shown great potential in medical images. 23,24 It can automatically extract high-level features from pixel images for tumor classification, segmentation and detection.…”
Section: Introductionmentioning
confidence: 99%
“… 15 , 17–21 However, hand-crafted features are low-order and susceptible to noise, and may not be adequate for unveiling the characteristics of tumors. 22 …”
Section: Introductionmentioning
confidence: 99%